Comprehensive review of innovative construction technology of high‐core rockfill dam: Nuozhadu project - Biao Liu; Zongliang Zhang; Lei Yan; Chao Liu; Mingxin Wu; Yuzhen Yu; Daren Zhang (River, 2025)
Abstract Underpinned by the ultrahigh‐core rockfill dam at the Nuozhadu Hydropower Station, comprehensive studies and engineering practices have been conducted to address several critical challenges: coordination of seepage deformation in dam materials, prevention and control of high‐water‐pressure seepage failure, static and dynamic deformation control, and construction quality monitoring. Advanced technologies have been developed for modifying impermeable soil materials and utilizing soft rocks. Constitutive models and high‐performance fine computational methods for dam materials have been improved, along with innovative seismic safety measures. Additionally, a “Digital Dam” and an information system for monitoring the construction quality were implemented. These efforts ensured the successful construction of the Nuozhadu Dam, making it the tallest dam in China and the third tallest dam in the world upon completion. This achievement increased the height of core dams in China by 100 m and established a design and safety evaluation framework for ultrahigh‐core rockfill dams exceeding 300 m in height. Furthermore, the current safety monitoring results indicate that the Nuozhadu Dam is safe and controllable.